2005
DOI: 10.1002/ca.20055
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of the cervical sympathetic trunk

Abstract: Lack of knowledge of the anatomy of the cervical sympathetic trunk (CST) may complicate surgical procedures on the cervical spine. This study aims to define linear and angular relations of the CST with respect to consistent structures around it, including the number and size of the cervical ganglia, the distances between the CST and the longus colli muscle and the anterior tubercles of the transverse processes of cervical vertebrae. Morphometric parameters of the 24 CSTs of 12 adults were measured on both side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 16 publications
(24 reference statements)
4
76
1
2
Order By: Relevance
“…The diameter at this site was reported to be 3-4 mm by Lyons and Mills [12], 2.7 ± 0.6 mm by Ebraheim et al [5], and 2.2 ± 0.7 mm by Kıray et al [11].…”
Section: Discussionmentioning
confidence: 86%
“…The diameter at this site was reported to be 3-4 mm by Lyons and Mills [12], 2.7 ± 0.6 mm by Ebraheim et al [5], and 2.2 ± 0.7 mm by Kıray et al [11].…”
Section: Discussionmentioning
confidence: 86%
“…vertebral ganglion were each observed in 33.3%. There was no difference between the number of superior and vertebral ganglia between the right and left sides (Kiray et al, 2005). The superior cervical ganglion was observed in all cases (100%), the MG was observed on 91.7%, and the vertebral ganglion was observed on 94.4% cases (Kawashima, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…The route to the anterior cervical spine through a corridor surrounded by carotid artery laterally, and trachea and oesophagus medially, was realized to be safe (Cloward, 1958). Today it is used more commonly for the surgical treatment of other cervical spine diseases including cervical spondylotic myelopathy, tumor, infection, or trauma of the vertebral bodies (Kiray et al, 2005). The most frequent complication secondary to anterior approach has been known as the injury of the recurrent laryngeal and superior laryngeal nerves resulting in vocal cord paralysis (Smith and Robinson, 1958;Cloward, 1962;Jacobson, 1979;Saunders et al, 1991;An et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Pick [5] reported double middle cervical ganglion. Kiray et al [6], Ebraheim et al [7] and Katritsis et al [8] reported the incidence of middle cervical ganglion as 33.3%, 39.3% and 53.2% respectively. Ebraheim et al [7] reported the length and width of middle cervical ganglion as 9.7±2.1mm and 5.2±1.3mm, Kiray et al [6] reported mean length as 9.7±3.4mm and mean width as 5.0±1.1mm whereas the present case showed the length of middle cervical ganglion to be and mean width to be 5 mm, which was comparatively much higher than that reported by others.…”
Section: Discussionmentioning
confidence: 99%